On ξs-quadratic stochastic operators in 2-dimensional simplex - Mukhamedov, Farrukh; Mohd Jamal, Afifah Hanum (2010)

(untitled)
In this paper we introduce a new class of quadratic stochastic operators called xi-s-QSO. We first classify such operators on 2D-simplex, into six non-isomorphic classes, with respect to their conjugacy and renumeration of the coordinates. Moreover, we investigate the behaviour of operators from two classes.